Strategi Komunikasi Pengurus Pesantren Dalam Meningkatkan Motivasi Belajar Santri Darussalam Blokagung 2 Desa Setail Kecamatan Genteng Kabupaten Banyuwangi - Agus Baihaqi; Ahmad Ali Musyaffa’ Fil Waro (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Communication in education is a very important element and has a very large role. Effective communication in education is very necessary, communication can be considered effective and conducive when the communicant can receive and understand the contents of the message conveyed by the communicator. Communication strategies are very important to learn for Islamic boarding school administrators in order to achieve messages or learning motivation effectively. However, not all Islamic boarding school administrators can create good communication strategies, sometimes administrators even ignore the communication aspect where Islamic boarding school administrators only convey messages without thinking about how the message can be received well by students. The purpose of this study was to determine the communication strategies used by Islamic boarding school administrators to motivate students to learn Darussalam Blokagung 2 Setail Village, Genteng District, Banyuwangi Regency. And to determine the supporting and inhibiting factors of the communication strategy of Islamic boarding school administrators. The type of research used by the researcher is qualitative research. This research is classified into the type of field research. The approach that the researcher will use is a descriptive approach. To test the validity of the data, the researcher uses extended observation, increases persistence, and triangulation. All data that has been collected is analyzed using data collection analysis, data reduction, data display, and drawing conclusions. The results of the study show that effective communication strategies and providing positive feedback are the main keys to increasing students' learning motivation at the Darussalam Blokagung 2 Islamic Boarding School, Setail Village, Genteng District. These supporting factors create a positive learning environment, support the development of students, and motivate them to achieve higher achievements.